2010
DOI: 10.1088/0031-8949/2010/t142/014003
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale effects on the decay of rotating helical and non-helical turbulence

Abstract: Decaying three-dimensional (3D) turbulence is studied via direct numerical simulations (DNS) for an isotropic non-rotating flow and for rotating flows with and without helicity. We analyze the cases of moderate Rossby number and large Reynolds number focusing on the behavior of the energy spectrum at large scales and studying its effect on the time evolution of the energy and integral scales for E(k) ∼ k 4 initial conditions. In the non-rotating case we observe the classical energy decay rate t −10/7 and a gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…The purpose of simulations A and C is to recover well known results for isotropic ∼ k 2 and ∼ k 4 turbulence, and to use them as a starting point to analyze the more complex rotating cases. Note the decay of ∼ k 4 turbulence (corresponding to runs C and D) was studied in detail in [26], and is considered here to compare with the ∼ k 2 case.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of simulations A and C is to recover well known results for isotropic ∼ k 2 and ∼ k 4 turbulence, and to use them as a starting point to analyze the more complex rotating cases. Note the decay of ∼ k 4 turbulence (corresponding to runs C and D) was studied in detail in [26], and is considered here to compare with the ∼ k 2 case.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Numerical simulations and models also show a slow down of the energy decay for many different initial conditions [11,[20][21][22][23][24], together with the trend towards two-dimensionalization [22,25], and the higher cyclonic-over-anticyclonic activity [26,27]. The first theoretical study of the decay of rotating turbulence was reported in [28], and considered the decrease of the energy transfer in the presence of rotation to explain the observed slow down in the decay, and to predict decay rates for the energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth pointing out that these quantities were also shown to be conserved in other systems: proofs of the conservation of K and I 2D for quasigeostrophic flows can be found in [50]. In practice, these quantities are only approximately conserved in numerical simulations, see e.g., the approximate constancy of I 2D and K reported for rotating flows in [47].…”
Section: Unboundedmentioning
confidence: 94%
“…The increase of computational power has also allowed the study of rotating flows by simulations. Most numerical investigations have focused on decaying turbulence (Bardina, Ferziger & Rogallo 1985;Mansour, Gambon & Speziale 1992;Bartello, Metais & Lesieur 1994;Hossain 1994;Squires et al 1994;Godeferd & Lollini 1999;Smith & Waleffe 1999;Morinishi, Nakabayashi & Ren 2001;Müller & Thiele 2007;Thiele & Müller 2009;Teitelbaum & Mininni 2010;Yoshimatsu, Midorikawa & Kaneda 2011), with more recent investigations of forced rotating turbulence both at large scales (Yeung & Zhou 1998;Mininni, Alexakis & Pouquet 2009;) and at small scales in order to observe the development of an inverse cascade (Smith & Waleffe 1999;Teitelbaum & Mininni 2009). Computational cost however did not allow for an exhaustive coverage of the parameter space.…”
Section: Introductionmentioning
confidence: 99%